Augmentation therapy with tandospirone citrate in vascular depression patients with mild cognitive impairment: A prospective randomized clinical trial. (March 2023) - Chen, Ronghua; Lin, Qianwen; Wu, Juan; Lin, Yongsen; Lin, Ting; Wu, Weiwei; Chen, Xinyan; Wu, Shufang; Zeng, Guiying; Lin, Xiaohui; Wu, Yongxi; Liu, Nan; et al.
Abstract: Cognitive impairment is a prominent clinical manifestation of vascular depression (VaDep). The current study aimed to assess the efficacy of tandospirone citrate in VaDep cases with mild cognitive impairment (VaDep-MCI) as well as the role of plasma monoamine neurotransmitters during the treatment. In this single-blind, randomized controlled study, 116 participants were randomly assigned to the tandospirone (tandospirone citrate-escitalopram) and control (escitalopram) groups. The primary endpoints were changes in cognitive test scores from baseline to Week 8, including the Rey Auditory Verbal Learning Test (RAVLT), Semantic Verbal Fluency (SVF) test, Trail Making Test (TMT), Digital Span Test (DST) and Clock Drawing Test (CDT) scores. Generalized estimating equation models were used to examine repeated measures. The results showed that compared with the changes in the control group from baseline to Week 8, the tandospirone group showed more significant changes in SVF score at Weeks 4 ( p  < 0.05) and 8 ( p  < 0.001), and TMT (B-A) score at Week 8 ( p  < 0.05). RAVLT, DST and DCT scores were relatively stable in both groups during the study period. Moreover, mediation analysis showed that these results were not mediated by the alleviation of depression symptoms. Partial Spearman correlation analysis showed that only plasma 5-hydroxytryptamine (5-HT) was positively correlated with Hamilton Depression Rating Scale score after Bonferroni correction ( r  = 0.347, p  < 0.001). Augmentation therapy with tandospirone citrate improved the executive and language functions of VaDep-MCI patients. Additionally, plasma 5-HT levels may serve as a potential biomarker of VaDep severity. These findings may provide clinical insights into the treatment of vascular depression.